Pemberdayaan Masyarakat Pada UKM Depo Air Minum Tirta Barokah Dan Bakso Tuna Cintaku - Hatneny, Aleria Irma; Mahardani, Ahmad Subhan; Saraswati, Ety (University of Islam Malang, 2019)
Indonesia has a large fishery resource, since most of the area covered by oceans. Therefore, the availability of national fish is enough to support the needs of the fish processing industry. The fishery potential can be a challenge for the people of the coastal area to convert it into a product that has economic value added. The potential of fishery resources in the coastal south, Village Sitiarjo, District Sumbermanjing Wetan, Malang district has not received empowerment program well. The majority of people in the region still lags behind economically. The Community Service Program was aimed to make economic empowerment of the target society of SME-based on fish meatballs production and drinking water depots. The implementation methods were carried out in several stages: data collection, planning, implementation, monitoring, feedback, and final evaluation. The model implemented was intensive training and assistance to obtain the maximum output corresponding to the objectives of the community service program. The results of this community service are to encourage the fish processing industry in the area to improve people's welfare and to overcome the problem of the water crisis in the target communities.